A method for constructing a structure optimization direction and a structure parameter optimization range of a Ti-doped CeO2 composite oxide catalyst
Patent Information
- Application Number
- CN202611377645.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-30
AI Technical Summary
上述优化方式虽然能够在一定程度上改善催化剂性能,但难以明确不同结构参数对氯苯氧化性能的贡献关系,也难以确定催化剂的整体结构调控方向
与现有技术相比,本发明不是仅对催化剂的单一结构参数进行调节,而是先确定适用于氯苯催化氧化反应的催化剂结构优化方向,进一步将结构优化方向量化为Lewis酸位点、表面活性氧物种、Ce3+相关缺陷结构、有效表面暴露以及相关受控结构参数的协同优化范围,并以协同优化范围界定Ti掺杂CeO2复合氧化物催化剂的有效结构状态。
Smart Images

Figure CN123017221A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chlorobenzene catalytic oxidation technology, specifically relating to a method for constructing the structural optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst. Background Technology
[0002] Chlorobenzene is a typical halogenated volatile organic compound (VOC) widely used in pesticide manufacturing and pharmaceutical intermediate production processes. It easily volatilizes into the environment during transportation, storage, and use, causing persistent environmental pollution. Furthermore, the chlorine atom increases molecular polarity, making it highly biotoxic. Chlorobenzene can further transform into even more toxic products such as polychlorinated aromatic hydrocarbons and dioxins. Therefore, chlorobenzene has become a typical pollutant in the field of volatile organic compound remediation.
[0003] Existing chlorobenzene purification technologies, including absorption, adsorption, and plasma methods, cannot meet the requirements of high efficiency, safety, and low energy consumption. In contrast, catalytic oxidation technology can convert pollutants into CO2 and H2O at low temperatures, making it the most promising VOCs purification technology. However, existing catalysts generally suffer from insufficient low-temperature activity, poor long-term stability, and inability to adapt to complex operating conditions.
[0004] Ti-doped CeO2 composite oxide catalysts can be used for the catalytic oxidation of chlorobenzene. Current optimization techniques for Ti-doped CeO2 composite oxide catalysts primarily focus on single aspects such as Ce / Ti ratio adjustment, heat treatment condition adjustment, morphology control, pore structure adjustment, or defect control. While these optimization methods can improve catalyst performance to some extent, they struggle to clearly define the contribution relationship between different structural parameters to chlorobenzene oxidation performance and determine the overall direction of catalyst structure control.
[0005] Therefore, how to determine the positive and negative factors affecting the chlorobenzene oxidation performance of Ti-doped CeO2 composite oxide catalysts based on activity testing and physicochemical characterization, and to construct the direction of catalyst structure optimization and the range of structural parameter optimization accordingly, is a problem that needs to be solved by those skilled in the art. Summary of the Invention
[0006] To address the problems existing in the prior art, this invention provides a method for constructing the structural optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst.
[0007] The technical solution adopted by this invention to solve the technical problem is as follows: The present invention provides a method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst, which mainly includes the following steps: S1: Prepare a group of Ti-doped CeO2 composite oxide catalyst samples with different structural characteristics; S2: The Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 was subjected to chlorobenzene catalytic oxidation activity test to obtain activity indicators reflecting the chlorobenzene oxidation performance of the catalyst. S3: Characterize the physicochemical properties of the Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 to obtain structural parameters that reflect the surface acidity, surface oxygen species, defect structure and surface exposure characteristics of the catalyst. S4: The activity index obtained in step S2 and the structural parameters obtained in step S3 are used to identify the multi-factor contribution and determine the positive and negative factors related to the chlorobenzene oxidation performance of the catalyst. S5: Based on the positive and negative activity correlation factors obtained in step S4, determine the structural optimization direction of the Ti-doped CeO2 composite oxide catalyst; S6: Determine the corresponding structural parameter optimization range based on the structural optimization direction obtained in step S5.
[0008] Furthermore, in step S1, by adjusting the Ti doping ratio and heat treatment conditions, Ti-doped CeO2 composite oxide catalyst samples with different surface acidity, surface oxygen species, defect structures and surface exposure characteristics are formed.
[0009] Furthermore, in step S2, the activity index includes T 20 and T 90 The T 20 The T value represents the reaction temperature at which the chlorobenzene conversion reaches 20%. 90 This indicates the reaction temperature at which the chlorobenzene conversion rate reaches 90%.
[0010] Further, in step S3, the physicochemical property characterization is selected from one or more of surface acidity characterization, surface oxygen species characterization, defect structure characterization, and surface exposure characteristic characterization; the surface acidity characterization is used to obtain the distribution of acidic sites on the catalyst surface, including NH3 temperature-programmed desorption testing and NH3 adsorption in-situ infrared testing; surface acid parameters are obtained through surface acidity characterization, and the surface acid parameters are selected from one or more of Lewis acid site content, Brønsted acid site content, weak acid site content, medium-strong acid site content, and strong acid site content; the surface oxygen species characterization is used to obtain the distribution of oxygen species on the catalyst surface, including X-ray photoelectron spectroscopy testing and O2 temperature-programmed desorption testing; surface oxygen species parameters are obtained through surface oxygen species characterization, and the surface oxygen species parameters are selected from one or more of surface adsorbed oxygen content, surface lattice oxygen content, bulk lattice oxygen content, and surface hydroxyl oxygen content; the defect structure characterization is used to obtain the surface oxygen species content in the catalyst and Ce 3+ Relevant defect structure parameters, including X-ray photoelectron spectroscopy and electron paramagnetic resonance (EPR) measurements, were obtained through defect structure characterization. These defect structure parameters were selected from Ce... 3+ Content, Ce 4+ Content, Ce 3+ / Ce 4+ One or more of the ratio and oxygen vacancy signal intensity; the surface exposure characterization is used to obtain the effective reaction interface and pore structure parameters of the catalyst, including N2 adsorption-desorption test; the surface exposure characteristic parameters obtained by surface exposure characterization are selected from one or more of specific surface area, pore volume and average pore size.
[0011] Furthermore, in step S3, the physicochemical property characterization also includes reduction performance characterization, which includes H2 programmed temperature reduction test to obtain the reduction performance parameters of the catalyst and to help determine the migration ability and redox ability of active oxygen species on the catalyst surface.
[0012] Furthermore, in step S4, the multi-factor contribution identification is selected from one or more of correlation analysis, principal component analysis, and correlation contribution analysis; by identifying the multi-factor contribution, the activity index is correlated with surface acidity parameters, surface oxygen species parameters, defect structure parameters, and surface exposure characteristic parameters, thereby determining the key structural factors affecting the chlorobenzene oxidation performance of the catalyst.
[0013] Furthermore, in step S4, the positively correlated factors of activity are selected from Lewis acid sites, specific surface area, surface lattice oxygen, surface adsorbed oxygen, and Ce. 3+ / Ce 4+The ratio, medium-strong acid sites, pore volume, and medium-strong acid sites are selected from one or more of the following: the activity-related inverse factor is selected from one or more of the following: Brønsted acid sites, bulk lattice oxygen, surface hydroxyl oxygen, average pore size, grain size, strong acid sites, and weak acid sites.
[0014] Furthermore, in step S5, the structural optimization direction is: increasing the proportion of Lewis acid sites, enriching surface reactive oxygen species, and enhancing Ce. 3+ Related defect structures are identified and effective surface exposure is maintained; meanwhile, the proportions of Brønsted acid sites, bulk lattice oxygen content, surface hydroxyl oxygen content, average pore size, grain size, strong acid site content, and weak acid site content are controlled.
[0015] Furthermore, in step S6, the structural parameter optimization range includes the structural parameter optimization range that needs to be enhanced and the structural parameter optimization range that needs to be controlled; the structural parameter optimization range that needs to be enhanced is: Lewis acid site content ratio of 74.1%-86.6%, and specific surface area of 98.8-159.9 m². 2 / g, the surface lattice oxygen content accounts for 64.3%-72.4%, the surface adsorbed oxygen content accounts for 30.7%-35.0%, Ce 3+ / Ce 4+ The ratio is 0.21-0.25, and the pore volume is 0.13-0.15 cm³. 3 / g, the content of medium and strong acid sites is 35.0%-42.6%; the optimized range of the structural parameters to be controlled is: the content of Brønsted acid sites is 13.4%-25.9%, the content of bulk lattice oxygen is 27.6%-35.7%, the content of surface hydroxyl oxygen is 7.0%-11.5%, the average pore size is 3.6-6.0nm, the grain size is 3.8-8.7nm, the content of strong acid sites is 27.9%-34.4%, and the content of weak acid sites is 24.2%-33.6%.
[0016] This invention provides a method for constructing the structural optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst, thereby obtaining a Ti-doped CeO2 composite oxide catalyst.
[0017] This invention provides a Ti-doped CeO2 composite oxide catalyst, which has the following properties: Lewis acid site content, specific surface area, surface lattice oxygen content, surface adsorbed oxygen content, and CeO2 content. 3+ / Ce 4+The ratio, pore volume, and proportion of medium- and strong acid sites are all within the optimization range of the structural parameters that need to be enhanced; the proportion of Brønsted acid sites, the proportion of bulk lattice oxygen content, the proportion of surface hydroxyl oxygen content, the average pore size, the grain size, the proportion of strong acid sites, and the proportion of weak acid sites are all within the optimization range of the structural parameters that need to be controlled.
[0018] The beneficial effects of this invention are: Compared with existing technologies, this invention does not merely adjust a single structural parameter of the catalyst, but first determines the direction of catalyst structure optimization suitable for the catalytic oxidation of chlorobenzene, and further quantifies the direction of structure optimization into Lewis acid sites, surface active oxygen species, and Ce. 3+ The synergistic optimization range of related defect structures, effective surface exposure, and related controlled structural parameters is determined, and the effective structural state of Ti-doped CeO2 composite oxide catalyst is defined by the synergistic optimization range.
[0019] This multi-parameter synergistic optimization strategy overcomes the performance bottleneck caused by single-variable regulation in traditional methods, enabling more precise matching of the comprehensive requirements of chlorobenzene catalytic oxidation reaction on catalyst surface acidity, redox capacity, and mass transfer characteristics. By clarifying the optimization range of each key structural parameter, this invention effectively improves the chlorobenzene oxidation performance of Ti-doped CeO2 composite oxide catalysts, solving the technical challenge of balancing activity and selectivity in practical applications of existing Ti-doped CeO2 composite oxide catalysts. This provides a clear theoretical basis and technical guidance for the design and preparation of high-performance chlorobenzene oxidation catalysts. Attached Figure Description
[0020] Figure 1 The results of Pearson correlation analysis of the activity index and structural parameters of the catalyst samples prepared in Example 1 and Comparative Examples 1-6 are shown.
[0021] Figure 2 The results of principal component analysis of the activity index and structural parameters of the catalyst samples prepared in Example 1 and Comparative Examples 1-6 are shown.
[0022] Figure 3 The results show the long-term stability test results of the Ti-doped CeO2 composite oxide catalyst sample prepared in Example 1.
[0023] Figure 4 The results show the long-term water resistance test results of the Ti-doped CeO2 composite oxide catalyst sample prepared in Example 1. Detailed Implementation
[0024] In a first aspect, the present invention provides a method for constructing the structural optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst.
[0025] The present invention provides a method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst, the specific implementation process of which is as follows: Step S1: Prepare a group of Ti-doped CeO2 composite oxide catalyst samples with different structural characteristics.
[0026] Specifically, Ti-doped CeO2 composite oxide catalyst samples can be obtained by adjusting the Ti doping ratio and heat treatment conditions to form a group of Ti-doped CeO2 composite oxide catalyst samples with different surface acidity, surface oxygen species, defect structures, and surface exposure characteristics. It should be noted that adjusting the Ti doping ratio and heat treatment conditions is only used to construct Ti-doped CeO2 composite oxide catalyst sample groups with structural differences, in order to further determine the direction of catalyst structure optimization.
[0027] Step S2: The Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 is subjected to chlorobenzene catalytic oxidation activity test to obtain activity indicators reflecting the chlorobenzene oxidation performance of the catalyst.
[0028] Specifically, the activity indicators mainly include T 20 and T 90 Among them, T 20 T represents the reaction temperature at which the chlorobenzene conversion reaches 20%. 90 This indicates the reaction temperature at which the chlorobenzene conversion rate reaches 90%.
[0029] Step S3: Characterize the physicochemical properties of the Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 to obtain structural parameters reflecting the surface acidity, surface oxygen species, defect structure, and surface exposure characteristics of the catalyst.
[0030] Specifically, the physicochemical property characterization is selected from one or more of the following: surface acidity characterization, surface oxygen species characterization, defect structure characterization, surface exposure characteristic characterization, and reduction performance characterization.
[0031] The surface acidity characterization mainly includes NH3 temperature-programmed desorption testing and NH3 adsorption in-situ infrared testing, primarily used to obtain the distribution of acidic sites on the catalyst surface. The surface acidity parameters obtained through surface acidity characterization are selected from one or more of the following: Lewis acid site content, Brønsted acid site content, weak acid site content, medium-strong acid site content, and strong acid site content.
[0032] Surface oxygen species characterization mainly includes X-ray photoelectron spectroscopy (XPS) and O2 temperature-programmed desorption (RTD) tests, primarily used to obtain the distribution of oxygen species on the catalyst surface. The surface oxygen species parameters obtained through characterization are selected from one or more of the following: surface adsorbed oxygen content, surface lattice oxygen content, bulk lattice oxygen content, and surface hydroxyl oxygen content.
[0033] The defect structure characterization mainly includes X-ray photoelectron spectroscopy and electron paramagnetic resonance (EPR) testing, primarily used to obtain information about Ce in the catalyst. 3+ Relevant defect structure parameters. The defect structure parameters obtained through defect structure characterization are selected from Ce... 3+ Content, Ce 4+ Content, Ce 3+ / Ce 4+ One or more of the ratio and oxygen vacancy signal intensity.
[0034] The surface exposure characterization mainly includes N2 adsorption-desorption testing, which is primarily used to obtain the effective reaction interface and pore structure parameters of the catalyst. The surface exposure characteristic parameters obtained through surface exposure characterization are selected from one or more of specific surface area, pore volume, and average pore size.
[0035] The reduction performance characterization mainly includes H2 temperature-programmed reduction testing, which is mainly used to obtain the reduction performance parameters of the catalyst and to help determine the migration ability and redox ability of active oxygen species on the catalyst surface.
[0036] Step S4: The activity index obtained in step S2 and the structural parameters obtained in step S3 are used to identify the contribution of multiple factors, and the positive and negative factors related to the chlorobenzene oxidation performance of the catalyst are determined.
[0037] Specifically, multi-factor contribution identification is selected from one or more of correlation analysis, principal component analysis, and correlation contribution analysis. Multi-factor contribution identification can correlate activity indicators with surface acidity parameters, surface oxygen species parameters, defect structure parameters, and surface exposure characteristic parameters, thereby identifying the key structural factors affecting the chlorobenzene oxidation performance of the catalyst.
[0038] Specifically, the positively correlated factors for activity are selected from Lewis acid sites, specific surface area, surface lattice oxygen, surface adsorbed oxygen, and Ce. 3+ / Ce 4+ One or more of the following: ratio, medium-strong acid site, pore volume, and medium-strong acid site.
[0039] Specifically, the activity-related inverse factors are selected from one or more of the following: Brønsted acid sites, bulk lattice oxygen, surface hydroxyl oxygen, average pore size, grain size, strong acid sites, and weak acid sites.
[0040] Step S5: Based on the positive and negative activity correlation factors obtained in step S4, determine the structural optimization direction of the Ti-doped CeO2 composite oxide catalyst.
[0041] Specifically, the main directions for structural optimization are: increasing the proportion of Lewis acid sites, enriching surface reactive oxygen species, and enhancing Ce. 3+ Related defect structures are identified and effective surface exposure is maintained; meanwhile, the proportions of Brønsted acid sites, bulk lattice oxygen content, surface hydroxyl oxygen content, average pore size, grain size, strong acid site content, and weak acid site content are controlled.
[0042] Among them, surface-active oxygen species mainly include surface lattice oxygen and surface-adsorbed oxygen; Ce 3+ The relevant defect structures mainly include Ce 3+ / Ce 4+ The defect structure corresponding to the increase in the ratio; the effective surface exposure is mainly selected from one or both of specific surface area and pore volume.
[0043] The structural optimization direction determined in this invention is not based on a single specific surface area, the proportion of a single acidic site, the content of a single oxygen species, or a single defect structural parameter. Instead, it is based on the synergistic matching between surface acidity, surface oxygen species, defect structures, and surface exposure characteristics. Therefore, this structural optimization direction can guide the subsequent structural regulation of catalysts and the design of chlorobenzene catalytic oxidation catalysts. Furthermore, based on this structural optimization direction, each activity-related structural factor can be quantitatively defined to obtain the structural parameter optimization range corresponding to the structural optimization direction.
[0044] Step S6: Determine the corresponding structural parameter optimization range based on the structural optimization direction obtained in step S5.
[0045] Specifically, the optimization range of structural parameters mainly includes the optimization range of structural parameters that need to be enhanced and the optimization range of structural parameters that need to be controlled.
[0046] The structural parameters requiring optimization are: Lewis acid site content of 74.1%-86.6% and specific surface area of 98.8-159.9 m². 2 / g, the surface lattice oxygen content accounts for 64.3%-72.4%, the surface adsorbed oxygen content accounts for 30.7%-35.0%, Ce 3+ / Ce 4+ The ratio is 0.21-0.25, and the pore volume is 0.13-0.15 cm³. 3 / g, with the content of medium-strong acid sites accounting for 35.0%-42.6%.
[0047] The optimized range of structural parameters to be controlled is as follows: Brønsted acid site content of 13.4%-25.9%, bulk lattice oxygen content of 27.6%-35.7%, surface hydroxyl oxygen content of 7.0%-11.5%, average pore size of 3.6-6.0 nm, grain size of 3.8-8.7 nm, strong acid site content of 27.9%-34.4%, and weak acid site content of 24.2%-33.6%.
[0048] It should be noted that the optimization range of structural parameters does not depend on a specific Ti to Ce atomic ratio, precursor type, preparation route, or heat treatment conditions. Instead, it is defined by whether the structural parameters synergistically satisfy the optimization range obtained in step S6 above. Ti-doped CeO2 composite oxide catalysts obtained through different control methods are acceptable as long as their structural parameters meet the above optimization range.
[0049] Secondly, the present invention provides a method for screening Ti-doped CeO2 composite oxide catalysts.
[0050] The present invention can combine the activity index reflecting the chlorobenzene oxidation performance of the catalyst obtained in step S2 and the multi-factor contribution identification results obtained in step S4 to screen Ti-doped CeO2 composite oxide catalyst samples, thereby obtaining Ti-doped CeO2 composite oxide catalysts with superior chlorobenzene catalytic oxidation performance.
[0051] Specifically, the multi-factor contribution identification results indicate that Lewis acid sites, specific surface area, surface lattice oxygen, surface adsorbed oxygen, and Ce are the main contributing factors. 3+ / Ce 4+ The ratio, medium-strong acid sites, and pore volume, which are positive factors related to activity, are strongly correlated with the second quadrant of principal component analysis. Therefore, the Ti-doped CeO2 composite oxide catalyst sample located in the second quadrant of principal component analysis exhibits superior chlorobenzene catalytic oxidation performance.
[0052] Specifically, the T of the dominant CeO2 composite oxide catalyst sample located in the second quadrant of the principal component analysis 20 Preferably, the temperature is 257.2-263.2℃, T 90 The preferred temperature is 378.0-439.0℃. The minimum and maximum values of each structural parameter in the CeO2 composite oxide catalyst sample are used as the boundary values to determine the optimized range of its structural parameters. This CeO2 composite oxide catalyst sample is only used to determine the boundary values of the optimized range of structural parameters and does not constitute a limitation on the specific composition, preparation route, or heat treatment conditions of the catalyst. The optimized range of structural parameters is used to define the synergistic effective structural state of the catalyst, rather than using any single structural parameter as the basis for judging the quality of the catalyst.
[0053] The core technology of this invention does not lie in limiting specific Ti doping ratios, precursor types, preparation routes, or heat treatment conditions. Adjusting the Ti doping ratio and heat treatment conditions are merely optional control methods to obtain the optimized range of structural parameters; Ti-doped CeO2 composite oxide catalysts obtained using different control methods can achieve the technical effects of this invention as long as their structural parameters meet the above-mentioned optimized range.
[0054] Thirdly, the present invention provides a Ti-doped CeO2 composite oxide catalyst.
[0055] Specifically, the Ti-doped CeO2 composite oxide catalyst provided by the present invention mainly includes Ti, Ce and O elements, with CeO2 as the main crystal phase and Ti element existing in the catalyst in a doped state. Its structural parameters meet the optimized range of structural parameters obtained in step S6.
[0056] Specifically, the content of Lewis acid sites, specific surface area, surface lattice oxygen content, surface adsorbed oxygen content, and CeO2 content of Ti-doped CeO2 composite oxide catalysts are analyzed. 3+ / Ce 4+ The ratio, pore volume, and proportion of medium-strong acid sites are all within the range of structural parameters that need to be optimized.
[0057] Specifically, the proportions of Brønsted acid sites, bulk lattice oxygen content, surface hydroxyl oxygen content, average pore size, grain size, strong acid site content, and weak acid site content of the Ti-doped CeO2 composite oxide catalyst are all within the range of structural parameters that need to be optimized.
[0058] In other words, Ti-doped CeO2 composite oxide catalysts with different compositions or preparation methods can be compared as long as they have the same content of Lewis acid sites, specific surface area, surface lattice oxygen content, surface adsorbed oxygen content, and CeO2 content. 3+ / Ce 4+ If the ratio, pore volume, proportion of medium-strong acid sites, proportion of Brønsted acid sites, proportion of bulk lattice oxygen content, proportion of surface hydroxyl oxygen content, average pore size, grain size, proportion of strong acid sites, and proportion of weak acid sites all meet the optimization range of the structural parameters obtained in step S6, then it can be used as the catalyst of the present invention.
[0059] The Ti-doped CeO2 composite oxide catalyst provided by this invention exhibits superior chlorobenzene catalytic oxidation performance through the synergistic matching of the above-mentioned structural parameters, which has strong chlorobenzene adsorption and activation ability, surface active oxygen participation ability, redox cycling ability, and effective reaction interface exposure ability.
[0060] Thirdly, the present invention provides a method for preparing a Ti-doped CeO2 composite oxide catalyst.
[0061] The present invention provides a method for preparing a Ti-doped CeO2 composite oxide catalyst, which can be prepared by hydrothermal-calcination method, and the specific implementation process is as follows: (1) Mix glycerol and isopropanol in a volume ratio of (7-10):50 and stir to obtain the first mixed solution; (2) Add cerium source (such as cerium nitrate hexahydrate) and titanium source (such as tetrabutyl titanate) to the first mixed solution according to the molar ratio of Ce to Ti (0.5-4):1 and continue stirring. After hydrothermal treatment at 120℃ for 48h, filter, wash and dry to obtain the precursor sample; (3) The precursor sample was calcined in air at a temperature of 300-700℃ to obtain Ti-doped CeO2 composite oxide catalyst.
[0062] Fourthly, this invention provides an application of a Ti-doped CeO2 composite oxide catalyst in the catalytic oxidation of chlorobenzene.
[0063] The present invention provides the application of a Ti-doped CeO2 composite oxide catalyst in the catalytic oxidation of chlorobenzene, wherein the reactants and the Ti-doped CeO2 composite oxide catalyst are subjected to the catalytic oxidation of chlorobenzene at a temperature of 150-500℃.
[0064] Specifically, the reaction feed gas contains chlorobenzene and O2, with N2 as the balance gas. The concentration of chlorobenzene is preferably controlled at 200-300 ppm; the volume fraction of O2 is preferably 6%-10%; and the gas hourly space velocity (GHSV) is preferably 30,000 h⁻¹. -1 -35000h -1 .
[0065] Fifthly, the present invention provides an application of a Ti-doped CeO2 composite oxide catalyst in the CB oxidation reaction under aqueous conditions.
[0066] This invention provides the application of a Ti-doped CeO2 composite oxide catalyst in the oxidation of chlorobenzene (CB) under aqueous conditions. The reactants and the Ti-doped CeO2 composite oxide catalyst were continuously reacted at temperatures of 150℃, 250℃, 350℃, and 400℃ for 40 hours, respectively. The Ti-doped CeO2 composite oxide catalyst still exhibited good chlorobenzene oxidation performance under aqueous conditions.
[0067] Specifically, the reaction feed gas contains chlorobenzene, O2, and H2O, with N2 as the balance gas. The concentration of chlorobenzene is preferably controlled at 200-300 ppm; the volume fraction of O2 is preferably 6%-10%; and the gas hourly space velocity (GHSV) is preferably 30,000 h⁻¹. -1 -35000h -1 The volume fraction of H2O is preferably 10%.
[0068] Specifically, at a reaction temperature of 150℃, the chlorobenzene conversion rate of the Ti-doped CeO2 composite oxide catalyst was significantly higher than that under anhydrous conditions after the addition of H2O; at a reaction temperature of 250℃, the chlorobenzene conversion rate of the Ti-doped CeO2 composite oxide catalyst was also significantly improved after the addition of H2O; at a reaction temperature of 350℃, the Ti-doped CeO2 composite oxide catalyst maintained a high chlorobenzene conversion rate under both aqueous and anhydrous conditions; and at a reaction temperature of 400℃, the Ti-doped CeO2 composite oxide catalyst still maintained a high chlorobenzene conversion rate under aqueous conditions.
[0069] Furthermore, during continuous reaction processes at 150℃, 250℃, 350℃, and 400℃, the Ti-doped CeO2 composite oxide catalyst did not exhibit significant deactivation in a water-containing atmosphere, demonstrating good water resistance and stability. This indicates that the Ti-doped CeO2 composite oxide catalyst can adapt to water-containing conditions.
[0070] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0071] In the following examples, unless otherwise specified, all component ratios are molar ratios. All units of measurement are well-known to those skilled in the art; for example, temperatures are in degrees Celsius (°C), time is in hours (h) or minutes (min), volume is in milliliters (ml), mass is in grams (g), and concentration is in ppm.
[0072] In the following embodiments, the experimental operations involved are all well known to those skilled in the art. For example, "hydrothermal treatment" refers to the process of placing the reactants in a closed reaction vessel and carrying out a liquid-phase reaction at a certain temperature; "calcination" refers to the process of heat-treating the sample in an air atmosphere.
[0073] In the following embodiments, the abbreviations used are all well known to those skilled in the art, such as: VOCs represents volatile organic compounds; CB represents chlorobenzene; GHSV represents gas hourly space velocity; 10 vol.% H2O represents 10% water vapor by volume.
[0074] In the following embodiments, the raw materials used, unless otherwise specified, can be obtained commercially and can be used directly. The experimental conditions and test methods not described in detail in the embodiments can be carried out by conventional methods in the art or according to the standard operating conditions provided by the relevant instrument and equipment suppliers.
[0075] Example 1 This embodiment provides a method for constructing the structural optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst. The specific implementation process is as follows: Step S1: Prepare Ti-doped CeO2 composite oxide catalyst samples; (1) Mix 7 mL of glycerol and 50 mL of isopropanol and stir at 500 rpm for 30 min to obtain the first mixed solution; (2) Add 0.025 mol cerium nitrate hexahydrate and 0.00833 mol tetrabutyl titanate to the first mixed solution, and continue stirring at 500 rpm for 60 min to obtain the second mixed solution; transfer the second mixed solution to a 100 mL polytetrafluoroethylene-lined reactor, and perform hydrothermal treatment at 120 °C for 48 h. After the reaction is completed, filter the obtained product, wash it with anhydrous ethanol, and dry it at 100 °C for 12 h to obtain the precursor sample; (3) The precursor sample was calcined in air at 500°C for 4 hours to obtain Ti-doped CeO2 composite oxide catalyst.
[0076] Step S2: The Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 is subjected to chlorobenzene catalytic oxidation activity test to obtain activity indicators reflecting the chlorobenzene oxidation performance of the catalyst.
[0077] The results show that the Ti-doped CeO2 composite oxide catalyst sample has a high T 20 The temperature was 257.2℃, T 90 At 386.5℃, it exhibits superior catalytic oxidation performance of chlorobenzene.
[0078] Step S3: Characterize the physicochemical properties of the Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 to obtain structural parameters reflecting the surface acidity, surface oxygen species, defect structure, and surface exposure characteristics of the catalyst.
[0079] The results showed that the Lewis acid site content of the Ti-doped CeO2 composite oxide catalyst sample was 74.1%, and the specific surface area was 98.8 m². 2 / g, the surface lattice oxygen content accounts for 72.4%, the surface adsorbed oxygen content accounts for 35.0%, Ce 3+ / Ce 4+ The ratio is 0.25, and the pore volume is 0.15 cm³. 3 The Ti-doped CeO2 composite oxide catalyst sample obtained in Example 1 has the following structural parameters: 40% of the medium-strong acid sites, 25.9% of the Brønsted acid sites, 27.6% of the bulk lattice oxygen content, 7.0% of the surface hydroxyl oxygen content, an average pore size of 6.0 nm, a grain size of 8.7 nm, 27.9% of the strong acid sites, and 33.6% of the weak acid sites. All structural parameters of the sample meet the above-mentioned optimized range.
[0080] Step S4: The activity index obtained in step S2 and the structural parameters obtained in step S3 are used to identify the contribution of multiple factors, and the positive and negative factors related to the chlorobenzene oxidation performance of the catalyst are determined.
[0081] Step S5: Based on the positive and negative activity correlation factors obtained in step S4, determine the structural optimization direction of the Ti-doped CeO2 composite oxide catalyst.
[0082] Step S6: Determine the corresponding structural parameter optimization range based on the structural optimization direction obtained in step S5.
[0083] Comparative Example 1 Sample No. 1 was operated the same as in Example 1 except that no titanium source was added.
[0084] Testing revealed that sample 1 contained 81.0% Lewis acid sites, had a specific surface area of 82.9 m² / g, a surface lattice oxygen content of 74.4%, and a surface adsorbed oxygen content of 13.4%. Ce... 3+ / Ce 4+ The ratio is 0.17, the pore volume is 0.21 cm³ / g, the content of medium-strong acid sites is 41.2%; the content of Brønsted acid sites is 19.0%, the content of bulk lattice oxygen is 25.6%, the content of surface hydroxyl oxygen is 5.7%, the average pore size is 10.3 nm, the grain size is 9.3 nm, the content of strong acid sites is 37.4%, and the content of weak acid sites is 29.7%.
[0085] Sample No. 1 showed that the proportions of Lewis acid sites, moderately strong acid sites, Brønsted acid sites, and weak acid sites were all within the corresponding optimization ranges; however, the proportions of surface lattice oxygen content, surface adsorbed oxygen content, and Ce content were all within the optimization ranges. 3+ / Ce 4+ The ratio, specific surface area, pore volume, bulk lattice oxygen content ratio, surface hydroxyl oxygen content ratio, average pore size, grain size, and strong acid site content ratio were all outside the optimization range for the corresponding structural parameters. Therefore, the structural parameters of sample number 1 did not fully meet the above optimization range.
[0086] Comparative Example 2 Sample No. 2 was operated the same as in Example 1, except that the relative amounts of Ti and Ce sources were adjusted to make the atomic ratio of Ti to Ce in the resulting catalyst 1:1.
[0087] Testing revealed that sample 2 contained 55.8% Lewis acid sites, had a specific surface area of 77.8 m² / g, a surface lattice oxygen content of 45.3%, and a surface adsorbed oxygen content of 16.8%. Ce... 3+ / Ce 4+ The ratio is 0.21, the pore volume is 0.086 cm³ / g, the content of medium-strong acid sites is 41.5%; the content of Brønsted acid sites is 44.2%, the content of bulk lattice oxygen is 54.7%, the content of surface hydroxyl oxygen is 7.4%, the average pore size is 4.4 nm, the grain size is 3.5 nm, the content of strong acid sites is 34.7%, and the content of weak acid sites is 30.3%.
[0088] Sample No. 2's surface hydroxyl oxygen content, medium-strong acid site content, average pore size, and weak acid site content are all within the optimized range for their respective structural parameters; however, the Lewis acid site content, surface adsorbed oxygen content, surface lattice oxygen content, and Ce content are all within the optimized range for their respective structural parameters. 3+ / Ce 4+ The ratio, specific surface area, pore volume, percentage of Brønsted acid sites, percentage of bulk lattice oxygen content, grain size, and percentage of strong acid sites were all outside the corresponding optimization range. Therefore, the structural parameters of sample number 2 did not fully meet the above optimization range.
[0089] Comparative Example 3 Sample number 3 was performed in the same manner as in Example 1, except that no cerium source was added.
[0090] Testing revealed that sample number 3 contained 52.0% Lewis acid sites, had a specific surface area of 51.9 m² / g, a surface lattice oxygen content of 69.7%, and a surface adsorbed oxygen content of 10.3%. Ce...3+ / Ce 4+ The ratio is 0, the pore volume is 0.2 cm³ / g, and the content of medium-strong acid sites accounts for 40.5%; the content of Brønsted acid sites accounts for 48.0%, the content of bulk lattice oxygen accounts for 30.3%, the content of surface hydroxyl oxygen accounts for 13.8%, the average pore size is 16.4 nm, the grain size is 15.7 nm, the content of strong acid sites accounts for 19.4%, and the content of weak acid sites accounts for 38.2%.
[0091] Sample No. 3's surface lattice oxygen content ratio, medium-strong acid site content ratio, and bulk lattice oxygen content ratio are all within the corresponding optimization range; however, the Lewis acid site content ratio, surface adsorbed oxygen content ratio, and Ce content ratio are all within the optimization range. 3+ The relevant defect structures, specific surface area, pore volume, percentage of Brønsted acid sites, percentage of surface hydroxyl oxygen content, average pore size, grain size, percentage of strong acid sites, and percentage of weak acid sites are all outside the optimization range of the corresponding structural parameters. Therefore, the structural parameters of sample number 3 do not fully meet the above optimization range.
[0092] Comparative Example 4 Sample No. 4 was operated the same as in Example 1, except that the calcination temperature was adjusted to 300℃.
[0093] Testing revealed that sample number 4 contained 86.6% Lewis acid sites, had a specific surface area of 159.9 m² / g, a surface lattice oxygen content of 64.3%, and a surface adsorbed oxygen content of 30.7%. Ce... 3+ / Ce 4+ The ratio is 0.24, the pore volume is 0.15 cm³ / g, the content of medium-strong acid sites is 38.5%; the content of Brønsted acid sites is 13.4%, the content of bulk lattice oxygen is 35.7%, the content of surface hydroxyl oxygen is 11.5%, the average pore size is 3.64 nm, the grain size is 3.83 nm, the content of strong acid sites is 34.4%, and the content of weak acid sites is 25.4%.
[0094] The percentage of Lewis acid sites, the percentage of surface adsorbed oxygen, the percentage of surface lattice oxygen, and Ce in sample number 4. 3+ / Ce 4+ The ratio, specific surface area, pore volume, and proportion of medium- and strong acid sites are all within the corresponding optimization range; the proportion of Brønsted acid sites, the proportion of bulk lattice oxygen content, the proportion of surface hydroxyl oxygen content, the average pore size, the grain size, the proportion of strong acid sites, and the proportion of weak acid sites are all within the optimization range of the structural parameters that need to be controlled. Therefore, all structural parameters of sample number 4 meet the above-mentioned optimization ranges.
[0095] Comparative Example 5 Sample number 5 was operated the same as in Example 1, except that the calcination temperature was adjusted to 400℃.
[0096] Testing revealed that sample number 5 contained 83.5% Lewis acid sites and had a specific surface area of 124.6 m². 2 / g, the surface lattice oxygen content accounts for 66.9%, the surface adsorbed oxygen content accounts for 35.0%, Ce 3+ / Ce 4+ The ratio is 0.25, the pore volume is 0.13 cm³ / g, the content of medium-strong acid sites is 37.0%; the content of Brønsted acid sites is 16.5%, the content of bulk lattice oxygen is 33.1%, the content of surface hydroxyl oxygen is 7.0%, the average pore size is 4.1 nm, the grain size is 5.2 nm, the content of strong acid sites is 33.2%, and the content of weak acid sites is 24.2%.
[0097] The percentage of Lewis acid sites, the percentage of surface adsorbed oxygen, the percentage of surface lattice oxygen, and Ce in sample number 5. 3+ / Ce 4+ The ratio, specific surface area, pore volume, and proportion of medium- and strong acid sites are all within the corresponding optimization ranges; the proportion of Brønsted acid sites, the proportion of bulk lattice oxygen content, the proportion of surface hydroxyl oxygen content, the average pore size, the grain size, the proportion of strong acid sites, and the proportion of weak acid sites are all within the optimization ranges of the structural parameters that need to be controlled. Therefore, all structural parameters of sample number 5 meet the above-mentioned optimization ranges.
[0098] Comparative Example 6 Sample number 6 was operated the same as in Example 1, except that the calcination temperature was adjusted to 600℃.
[0099] Testing revealed that sample number 6 contained 69.6% Lewis acid sites, had a specific surface area of 54.6 m² / g, a surface lattice oxygen content of 52.0%, and a surface adsorbed oxygen content of 26.0%. Ce... 3+ / Ce 4+ The ratio is 0.20, the pore volume is 0.10 cm³ / g, the content of medium-strong acid sites is 43.0%; the content of Brønsted acid sites is 30.4%, the content of bulk lattice oxygen is 48.0%, the content of surface hydroxyl oxygen is 18.0%, the average pore size is 7.5 nm, the grain size is 10.5 nm, the content of strong acid sites is 47.5%, and the content of weak acid sites is 20.1%.
[0100] The percentage of Lewis acid sites, the percentage of surface adsorbed oxygen, the percentage of surface lattice oxygen, and Ce in sample number 6. 3+ / Ce 4+ The ratio, specific surface area, pore volume, and proportion of medium- and strong acid sites were all outside the corresponding optimization range; the proportion of Brønsted acid sites, the proportion of bulk lattice oxygen content, the proportion of surface hydroxyl oxygen content, the average pore size, the grain size, the proportion of strong acid sites, and the proportion of weak acid sites were all outside the required optimization range for structural parameters. Therefore, the structural parameters of sample number 6 failed to meet the above-mentioned optimization range for structural parameters.
[0101] Experimental Example 1 This experimental example demonstrates the use of catalyst samples prepared in Example 1 and Comparative Examples 1-6 to undergo chlorobenzene oxidation at temperatures ranging from 150 to 500°C.
[0102] The catalyst sample loading was 0.2 g. Before the experiment, N2 was introduced into the fixed-bed reactor to purge other gas molecules and prevent interference. In this experiment, the simulated gas flow rate was 100 ml / min, and the GHSV was 32000 h⁻¹. -1 The mixture (containing 250 ppm chlorobenzene, 8% O2, and N2 as the equilibrium gas) was prepared in a mixing chamber. The inlet and outlet chlorobenzene concentrations were determined using a gas chromatograph (GC-4000A). The chlorobenzene conversion rate was calculated according to formula (1). The experimental results are shown in Table 1.
[0103] (1); In the formula, CB in The concentration of chlorobenzene at the inlet, CB out This represents the chlorobenzene outlet concentration.
[0104] Table 1. Catalytic oxidation activity of chlorobenzene for different catalyst samples
[0105] Samples 4 and 5, their Lewis acid site content percentage, surface adsorbed oxygen content percentage, surface lattice oxygen content percentage, Ce content percentage, 3+ / Ce 4+ The ratios, specific surface area, pore volume, and proportions of medium- and strong acid sites are all within the range of structural parameters that need to be enhanced. Furthermore, the proportions of Brønsted acid sites, bulk lattice oxygen content, surface hydroxyl oxygen content, average pore size, grain size, and the proportions of both strong and weak acid sites are all within the range of structural parameters that need to be controlled. Therefore, both sample number 4 and sample number 5 possess effective structural states that satisfy the aforementioned structural parameter optimization ranges.
[0106] Correspondingly, samples 4 and 5 both exhibited superior catalytic oxidation performance of chlorobenzene compared to the other comparative samples. Specifically, sample 4 showed better T... 20 The temperature was 260°C, only 3°C higher than in Example 1, and the lowest among the comparative samples; the T value of sample number 5 was... 90 The temperature was 378°C, lower than the 386°C in Example 1, and the lowest among the comparative samples. This indicates that when all structural parameters of the catalyst are within the optimized range described above, a lower ignition temperature and a lower high conversion temperature can be obtained.
[0107] In contrast, samples 1-3 and 6 all exhibited one or more structural parameters that deviated from the optimized range of the aforementioned structural parameters, and their T... 20 or T 90 The levels increased significantly. These results indicate that the catalytic oxidation performance of chlorobenzene is not determined by a single structural parameter, but rather depends on the Lewis acid sites, surface reactive oxygen species, and Ce... 3+ Coordination and matching among relevant defect structures, effective surface exposure, and relevant controlled structural parameters.
[0108] Experiment Example 2 This experimental example is used to characterize the physicochemical properties and identify the contributions of multiple factors to the catalyst samples prepared in Example 1 and Comparative Examples 1-6.
[0109] (1) The physicochemical properties of the catalyst samples prepared in Example 1 and Comparative Examples 1-6 were characterized to obtain structural parameters reflecting the surface acidity, surface oxygen species, defect structure and surface exposure characteristics of the catalyst.
[0110] Physicochemical characterization was performed using one or more of the following methods: NH3 temperature-programmed desorption test, NH3 adsorption in-situ infrared spectroscopy, X-ray photoelectron spectroscopy, O2 temperature-programmed desorption test, electron paramagnetic resonance spectroscopy, N2 adsorption-desorption test, and H2 temperature-programmed reduction test. The distribution of acidic sites on the catalyst sample surface could be obtained through NH3 temperature-programmed desorption test and NH3 adsorption in-situ infrared spectroscopy; the Ce content on the catalyst sample surface could be obtained through X-ray photoelectron spectroscopy. 3+ Content, Ce 4+ The content of oxygen, surface adsorbed oxygen, surface lattice oxygen, and surface hydroxyl oxygen can be obtained. The relative distribution of surface lattice oxygen and bulk lattice oxygen in the catalyst sample can be obtained by O2 temperature-programmed desorption test. The signal intensity of oxygen vacancy-related defect structures in the catalyst sample can be obtained by electron paramagnetic resonance test. The specific surface area, pore volume, and average pore size of the catalyst can be obtained by N2 adsorption-desorption test. The reduction performance parameters of the catalyst sample can be obtained by H2 temperature-programmed reduction test.
[0111] (2) The activity index of the catalyst samples prepared in Example 1 and Comparative Examples 1-6 was subjected to Pearson correlation analysis, principal component analysis and correlation contribution analysis with the above structural parameters.
[0112] The results of the Pearson correlation analysis are shown below. Figure 1 , of which O S-latt Represents the lattice oxygen content and O content of the catalyst surface. L-latt Represents the oxygen content and O content of the catalyst bulk lattice. ads Represents the oxygen content adsorbed on the catalyst surface, O -OH Aw represents the content of hydroxyl groups on the catalyst surface, Aw represents the content of weak acid sites on the catalyst, and A represents the content of weak acid sites on the catalyst surface. M Represents the content of strong acid sites in the catalyst, A S Represents the content of strong acid sites in the catalyst, A Br Represents the content of Brønsted acid sites in the catalyst, A Le Represents the content of Lewis acid sites in the catalyst, S BET Represents the specific surface area of the catalyst, A P Represents the average pore size of the catalyst, V P The average pore volume of the catalyst is represented by D, and the particle size of the catalyst is represented by D. Figure 1 It can be seen that surface adsorption of oxygen and Ce 3+ / Ce 4+ Parameters such as ratio, specific surface area, average pore size, grain size, and surface hydroxyl oxygen are related to T 20 T 90 There is a significant correlation between them, which can serve as a basis for subsequent identification of multi-factor contributions.
[0113] The results of principal component analysis are shown below. Figure 2 Surface adsorbed oxygen, surface lattice oxygen, Ce 3+ / Ce 4+ The ratios, specific surface area, medium-strong acid sites, pore volume, and Lewis acid sites are strongly correlated with superior chlorobenzene oxidation performance in the principal component space. These parameters can serve as positively correlated factors for improving the chlorobenzene oxidation performance of catalysts.
[0114] The results of principal component analysis are shown below. Figure 2 Brønsted acid sites, bulk lattice oxygen, surface hydroxyl oxygen, average pore size, grain size, strong acid sites, and weak acid sites are strongly correlated with lower catalytic performance in the principal component space. These parameters can be considered as inverse factors related to activity that need to be controlled during the improvement of chlorobenzene oxidation performance of the catalyst.
[0115] (3) Based on the principal component analysis results, the contribution of each physicochemical property parameter was identified, and the results are shown in Table 2.
[0116] Table 2. Identification of the contribution factors affecting the chlorobenzene oxidation performance of Ti-doped CeO2 composite oxide catalysts.
[0117] Based on the results shown in Table 1, the optimization direction for the Ti-doped CeO2 composite oxide catalyst was determined to be to enhance the positive factors of activity correlation and control the negative factors of activity correlation.
[0118] Experimental Example 3 In this experimental example, the Ti-doped CeO2 composite oxide catalyst prepared in Example 1 was continuously reacted at 150℃, 250℃, 350℃, and 400℃ for 40 hours, with each temperature point lasting 10 hours.
[0119] The relevant experimental conditions can be referred to in Experiment Example 1. The difference is that the outlet chlorobenzene concentration is measured every 30 minutes in this experiment.
[0120] The experimental results are as follows Figure 3 After 40 hours of continuous operation, the Ti-doped CeO2 composite oxide catalyst still maintains strong chlorobenzene oxidation performance.
[0121] Experiment Example 4 In this experimental example, the Ti-doped CeO2 composite oxide catalyst prepared in Example 1 was continuously reacted at 150℃, 250℃, 350℃, and 400℃ for 40 hours, with each temperature point lasting 10 hours.
[0122] The relevant experimental conditions can be referred to in Experiment Example 1. The difference is that the simulated gas in this invention also contains water vapor with a volume fraction of 10%.
[0123] The experimental results are as follows Figure 4 After running continuously for 40 hours under water vapor interference, the Ti-doped CeO2 composite oxide catalyst still maintains strong chlorobenzene oxidation performance.
[0124] This invention discloses a method for constructing a structure optimization direction and structural parameter optimization range for a Ti-doped CeO2 composite oxide catalyst. Those skilled in the art can refer to this document and appropriately improve the process parameters to achieve the desired result. It is particularly important to note that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention. The product of this invention has been described through preferred embodiments, and those skilled in the art can clearly modify or appropriately change and combine the product without departing from the content, spirit, and scope of this invention to realize and apply the technology of this invention.
Claims
1. A method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst, characterized in that, Includes the following steps: S1: Prepare a group of Ti-doped CeO2 composite oxide catalyst samples with different structural characteristics; S2: The Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 was subjected to chlorobenzene catalytic oxidation activity test to obtain activity indicators reflecting the chlorobenzene oxidation performance of the catalyst. S3: Characterize the physicochemical properties of the Ti-doped CeO2 composite oxide catalyst sample obtained in step S1 to obtain structural parameters that reflect the surface acidity, surface oxygen species, defect structure and surface exposure characteristics of the catalyst. S4: The activity index obtained in step S2 and the structural parameters obtained in step S3 are used to identify the multi-factor contribution and determine the positive and negative factors related to the chlorobenzene oxidation performance of the catalyst. S5: Based on the positive and negative activity correlation factors obtained in step S4, determine the structural optimization direction of the Ti-doped CeO2 composite oxide catalyst; S6: Determine the corresponding structural parameter optimization range based on the structural optimization direction obtained in step S5.
2. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S1, Ti-doped CeO2 composite oxide catalyst samples with different surface acidity, surface oxygen species, defect structures and surface exposure characteristics are formed by adjusting the Ti doping ratio and heat treatment conditions.
3. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S2, the activity index comprises T 20 and T 90 ; T 20 represents the reaction temperature corresponding to a chlorobenzene conversion of 20%, and T 90 represents the reaction temperature corresponding to a chlorobenzene conversion of 90%.
4. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S3, the physicochemical property characterization is selected from one or more of the following: surface acidity characterization, surface oxygen species characterization, defect structure characterization, and surface exposure characteristic characterization. The surface acidity characterization is used to obtain the distribution of acidic sites on the catalyst surface, including NH3 temperature-programmed desorption testing and NH3 adsorption in-situ infrared spectroscopy testing; surface acidity parameters are obtained through surface acidity characterization, and these parameters are selected from one or more of Lewis acid site content, Brønsted acid site content, weak acid site content, medium-strong acid site content, and strong acid site content; the surface oxygen species characterization is used to obtain the distribution of oxygen species on the catalyst surface, including X-ray photoelectron spectroscopy testing and O2 temperature-programmed desorption testing; Surface oxygen species parameters are obtained through surface oxygen species characterization, wherein the surface oxygen species parameters are selected from one or more of surface adsorbed oxygen content, surface lattice oxygen content, bulk lattice oxygen content, and surface hydroxyl oxygen content; The defect structure characterization is used to obtain Ce in the catalyst. 3+ Relevant defect structure parameters, including X-ray photoelectron spectroscopy and electron paramagnetic resonance (EPR) measurements, were obtained through defect structure characterization. These defect structure parameters were selected from Ce... 3+ Content, Ce 4+ Content, Ce 3+ / Ce 4+ One or more of the ratio and oxygen vacancy signal intensity; the surface exposure characterization is used to obtain the effective reaction interface and pore structure parameters of the catalyst, including N2 adsorption-desorption test; the surface exposure characteristic parameters obtained by surface exposure characterization are selected from one or more of specific surface area, pore volume and average pore size.
5. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S3, the physicochemical property characterization also includes reduction performance characterization, which includes H2 temperature-programmed reduction testing to obtain the reduction performance parameters of the catalyst and to help determine the migration ability and redox ability of active oxygen species on the catalyst surface.
6. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S4, the multi-factor contribution identification is selected from one or more of correlation analysis, principal component analysis, and correlation contribution analysis; by identifying the multi-factor contribution, the activity index is correlated with surface acidity parameters, surface oxygen species parameters, defect structure parameters, and surface exposure characteristic parameters, thereby determining the key structural factors affecting the chlorobenzene oxidation performance of the catalyst.
7. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S4, the positively correlated factors of activity are selected from Lewis acid sites, specific surface area, surface lattice oxygen, surface adsorbed oxygen, and Ce. 3+ / Ce 4+ The ratio, medium-strong acid sites, pore volume, and medium-strong acid sites are selected from one or more of the following: the activity-related inverse factor is selected from one or more of the following: Brønsted acid sites, bulk lattice oxygen, surface hydroxyl oxygen, average pore size, grain size, strong acid sites, and weak acid sites.
8. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S5, the structural optimization direction is: increasing the proportion of Lewis acid sites, enriching surface reactive oxygen species, and enhancing Ce. 3+ Related defect structures are identified and effective surface exposure is maintained; meanwhile, the proportions of Brønsted acid sites, bulk lattice oxygen content, surface hydroxyl oxygen content, average pore size, grain size, strong acid site content, and weak acid site content are controlled.
9. The method for constructing the structure optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst according to claim 1, characterized in that, In step S6, the structural parameter optimization range includes the structural parameter optimization range that needs to be enhanced and the structural parameter optimization range that needs to be controlled; the structural parameter optimization range that needs to be enhanced is: Lewis acid site content ratio of 74.1%-86.6%, and specific surface area of 98.8-159.9 m². 2 / g, the surface lattice oxygen content accounts for 64.3%-72.4%, the surface adsorbed oxygen content accounts for 30.7%-35.0%, Ce 3+ / Ce 4+ The ratio is 0.21-0.25, and the pore volume is 0.13-0.15 cm³. 3 / g, the content of medium and strong acid sites is 35.0%-42.6%; the optimized range of the structural parameters to be controlled is: the content of Brønsted acid sites is 13.4%-25.9%, the content of bulk lattice oxygen is 27.6%-35.7%, the content of surface hydroxyl oxygen is 7.0%-11.5%, the average pore size is 3.6-6.0nm, the grain size is 3.8-8.7nm, the content of strong acid sites is 27.9%-34.4%, and the content of weak acid sites is 24.2%-33.6%.
10. A Ti-doped CeO2 composite oxide catalyst obtained by the method for constructing the structural optimization direction and structural parameter optimization range of a Ti-doped CeO2 composite oxide catalyst as described in claim 9, characterized in that, The Lewis acid site content, specific surface area, surface lattice oxygen content, surface adsorbed oxygen content, and Ce content of the Ti-doped CeO2 composite oxide catalyst are described. 3+ / Ce 4+ The ratio, pore volume, and proportion of medium- and strong acid sites are all within the optimization range of the structural parameters that need to be enhanced; the proportion of Brønsted acid sites, the proportion of bulk lattice oxygen content, the proportion of surface hydroxyl oxygen content, the average pore size, the grain size, the proportion of strong acid sites, and the proportion of weak acid sites of the Ti-doped CeO2 composite oxide catalyst are all within the optimization range of the structural parameters that need to be controlled.